ANALISIS PROGRAM LISTRIK PEDESAAN DALAM MENINGKATKAN AKTIVITAS SOSIAL MASYARAKAT DI KECAMATAN DOLO KABUPATEN SIGI - Kali, Agustinus (MEKTEK, 2012)
Utilization of electric energy in rural communities will encourage increased productivity in agriculture and services sector, and stimulate growth of small and household industry the rural electrification program became one of the priorities of development in this decade. The importance of public knowledge aboutelectricity that includes productive activities, educational activities and social activities, especially in village of Langaleso Sub District Sigi Dolo done by studying the level of public understanding about electricity, know the effect of availability of electricity in rural areas of the knowledge society will be electricity, and evaluate the success of electric program countryside that have been implemented by the government. This research was conducted using methods through field surveys and interviews in the village of Dolo Kecamalan Langaleso to get the data (1) associated with general information and people, (2) information on economic and social activities in rural communities in question (3) the influence of rural electrification on the pattern of community life. Productive activities in village of Langaleso greatly enhanced by the existence of rural electrification as a light on the activities of kiosks, shops, small industries and industry household.